ANTI-NUCLEOSOME ANTIBODIES - A NOVEL TEST IN SYSTEMIC LUPUS ERYTHEMATOSUS - Horak, Pavel; Hermanova, Zuzana; Scudla, Vlastimil; Faltynek, Ladislav; Pospisil, Zdenek (Biomedical papers, 2000)
In this study the serum levels of specific anti-nucleosome autoantibodies (autoAb) were measured in the followup of the group of SLE patients and compared to the levels of anti-dsDNA, C3, C4 components of complement, toECLAM- European Lupus Activity Measure and to the levels of sVCAM-1, sICAM-1, neopterin, sIL-2r, IL-10 andfas ligand. Anti-nucleosome antibodies were detected using an enzyme immunoassay for the quantitative determinationof autoAb to nucleosomes and their components in the human serum in the group of 52 patients, 50 of themfemale, who all fulfilled criteria of SLE according to ACR (American Colledge of Rheumatology). Anti-nucleosomeantibodies were followed up during 3 subsequent measurements during six months and compared to the developmentof ECLAM index, the levels of anti ds-DNA antibodies and C3, C4 complement components levels and otheractivity markers.The probands with the stable low disease activity had the lowest levels of anti-nucleosome Ab (83 ±33.0 IU/ml).The patients with the stable high or increasing activity had the mean titers in the first series 200.42 ±36 IU/ml and192 ±65 IU/ml and 188±58.11 IU/ml in the 2. and 3. serial measurement. Subgroup with the high starting activityand with decrease of the activity index had the mean levels of 223 ±39.0IU/ml, 185.6 ±37.6 IU/ml and 207 ±55.5 IU/mlduring three measurements. In the subgroup of patients with lupus nephritis (LN) n=15, the anti-nucleosome Ablevels were 176 ±34.0 IU/ml, 174 ±30.0 IU/ml and 148±32.0 IU/ml. A strong correlation was found between levelsof anti-nucleosome and anti-dsDNA antibodies. All sera with anti-dsDNA antibodies over 40 had at the same timepositive titer of anti-nucleosome antibodies, however, 21 sera with negative anti-dsDNA had positive test for antinucleosomeantibodies. Anti-nucleosome antibodies correlated with ECLAM activity index and reversibly with C4.No correlation was established with levels of C3, sVCAM-1, sICAM-1, IL-10, fas ligand, neopterin and sIL2r. Theexamination of anti-nucleosome Ab contributes to the early diagnosis and is an instrument in the differentialdiagnosis of the connective tissue diseases and it seems to be especially valuable in anti-dsDNA negative lupus. Theuse of anti-nucleosome antibodies measurement as a marker of disease activity deserves further evaluation.
Keywords: Systemic lupus erythematosus (SLE) / Anti-nucleosome antibodies / ECLAM index / Thrombomodulin